2014
DOI: 10.1002/pbc.25102
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroid disease following alemtuzumab therapy and hematopoietic cell transplantation in pediatric patients with sickle cell disease

Abstract: Allogenic hematopoietic cell transplantation (alloHCT) is currently the only curative treatment option for patients with sickle cell disease. Alemtuzumab is a monoclonal antibody directed against CD52 positive cells used in myeloablative conditioning regimens for alloHCT. Its use has been associated with development of autoimmune disease in adult patients with rheumatologic conditions. We report on three cases of new onset autoimmune thyroid disease after alloHCT treatment with alemtuzumab in pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Alemtuzumab‐induced lymphopenia, with decreased CD4 + CD25 + regulatory T cells, may predispose to the development of autoimmunity. Autoimmune disease has been described after alemtuzumab administration for MS, rheumatic diseases, and post‐HCT . Many of the published cases have been in the MS population involving autoimmune thyroiditis and immune thrombocytopenic purpura .…”
Section: Safety and Toxicitiesmentioning
confidence: 99%
“…Alemtuzumab‐induced lymphopenia, with decreased CD4 + CD25 + regulatory T cells, may predispose to the development of autoimmunity. Autoimmune disease has been described after alemtuzumab administration for MS, rheumatic diseases, and post‐HCT . Many of the published cases have been in the MS population involving autoimmune thyroiditis and immune thrombocytopenic purpura .…”
Section: Safety and Toxicitiesmentioning
confidence: 99%
“…The mechanisms behind it are still uncertain, but it seems that thyroid dysfunction occurring after alemtuzumab therapy is an example of acquired autoimmunity . The study of Cox et al.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms behind it are still uncertain, but it seems that thyroid dysfunction occurring after alemtuzumab therapy is an example of acquired autoimmunity [6,12]. The study of Cox et al showed that after an initial depletion of lymphocytes, the B lymphocytes recovered earlier than T lymphocytes [14], making the patients more susceptible to autoimmunity [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…Alemtuzumab treatment is associated with an increased risk for the development of autoimmune diseases, for this reason a regular monitoring is indicated to allow for an early recognition and thereby early treatment of these diseases [10,17,19,[54][55][56][57]. Most of the autoimmune phenomena have a beneficial prognosis if they are identified early and anti-inflammatory treatment is started early.…”
Section: Post-infusion Monitoringmentioning
confidence: 99%